Outcomes of endoscopic third ventriculostomy in adults. (September 2016) - Lam, Sandi; Harris, Dominic A.; Lin, Yimo; Rocque, Brandon G.; Ham, Sandra; Pan, I-Wen
Highlights: This is an administrative database study of 525 endoscopic third ventriculostomy procedures in adults. The overall success rate of ETV in adult patients was 74.7%. Most of the ETV failures occurred within the first month after surgery. History of prior shunt and length of index hospital stay were associated with risk of ETV failure. Age, gender, and etiology of hydrocephalus were not associated with ETV failure. Abstract: Endoscopic third ventriculostomy (ETV) is an alternative to ventriculoperitoneal shunting for treatment of hydrocephalus. Studies have reported favorable outcomes for up to three-quarters of adult patients. We performed the first ETV outcomes study using an administrative claims database, examining current practice for adult patients in the United States. We interrogated the Truven Health MarketScan® database for Current Procedural Terminology codes corresponding to ETV and ventriculoperitoneal shunt from 2003- to 2011, including patients over 18 years and data from initial and subsequent hospitalizations. ETV failure was defined as any subsequent ETV or shunt procedure. Five hundred twenty-five patients underwent ETV with 6 months minimum follow-up. Mean age was 45.9 years (range: 18–86 years). Mean follow-up was 2.2 years (SD: 1.6 years, range: 0.5–8.4 years). Etiology of hydrocephalus was 21.3% tumor, 9.0% congenital/aqueductal stenosis, 15.8% hemorrhage, and 53.9% others. ETV was successful in 74.7% of patients. Of 133 who failed, 25 had repeat ETV; 108 had shunt placement. Longer length of stay for index surgery was associated with higher risk of failure (hazard ratio (HR): 1.03, p < 0.001), as was history of previous shunt (HR: 2.45, p < 0.001). Among patients with repeat surgeries, median time to failure was 25 days. This study represents a longitudinal analysis of nationwide ETV practice over 9 years. Success rate in this large cohort is similar to that published by other single-center retrospective studies. Age and geographic variation may be associated with surgeon choice of ETV or shunt placement after failure of the initial ETV.